Penggunaan Metode Difraksi Sinar-X Untuk Deteksi Perubahan Kristal Mineral Lempung Akibat Pemanasan dan Aktivasi =Study of X-ray Diffraction Method for Detecting Crystallinity Change in Clays due to Thermal and Activatio - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
ABSTRACT The effects of thermal and activation process on crystalline structure of clays from Boyolali and Riau were investigated using an X-ray diffraction method. The two treatments are expected to increase the crystallinity and stability of the crystal structure thereby improving the activity of the clays as absorbent catalysts and ion exchangers. The X-ray diffractog,rams showed that the Boyolali's clay js monmorilonit and Riau's clay is kaolinic. Heating from 600 to 1000 Â°C caused a damage to the monmorilonit crystal structure the decrease in crystallinity was proportional to the temperature increase. Similarly kaolinic crystallinity was destroyed at temperature higher than 600 Â°C. Activation increased the crystallinity of the monmorilonit, but caused destruction to kaolinic crystal. Hence, the two treatments have not brought appropriate conditions for improving the stability and crystallinity of the clays which requires further investigation. Key words : X-ray diffraction, clays, catalysts